Correlation Between Neutrophil–Lymphocyte Ratio and Inhospital Cardiac Events in Geriatric Patients With Hip Fractures - Miaomiao Yu; Zhen Cui; Ying Bai (Mediators of Inflammation)
Conclusion: Elevated preoperative NLR is an independent risk factor for postoperative inhospital MACEs in geriatric patients with hip fractures.